Cooked garlic and antioxidant activity: Correlation with organosulfur compound composition. (1st April 2017) - Locatelli, D.A.; Nazareno, M.A.; Fusari, C.M.; Camargo, A.B.
Highlights: Home cooked garlic retained antioxidant activity. Raw garlic evidenced mainly antiradical activity and ferric reducing capacity. Antioxidant mechanism was mostly demonstrated in stir-fried garlic samples. Antioxidant activities of home-cooked garlic were evaluated by five methodologies. Relationships were established among OSCs, garlic samples and antioxidant activities. Abstract: The antioxidant properties and the main beneficial organosulphur compounds of home-cooked garlic samples were studied in order to establish relationships between them. Antioxidant activity was tested by free radical scavenging against 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH ) and 2, 2′-azino-bis-(3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS + ), Fe(III) reducing ability (FRAP) and linoleic acid co-oxidation initiated by soybean lipoxygenase in a micelle system. DPPH, ABTS and FRAP assays showed the highest activity for raw garlic samples, while β -carotene bleaching assay yielded the highest activity for stir-fried garlic. Pure organosulphur compounds tested by DPPH, FRAP and β -carotene bleaching assays showed that allicin had an antiradical action mechanism, as well as iron reducing capacity; while antioxidant activity was the main mechanism for ajoenes and 2-VD. To our knowledge, this study is the first demonstration that home-cooked garlic retains its antioxidant activity, and, at the same time, elucidates the mechanisms involved in this activity.